Socialization of Applied Physics Textbook Writing for Teachers at SMK Pelayaran Padang - Yanti, Melda; Erlinda, Nelfi; Solehuddin, Solehuddin; Riyadi, Slamet; Bintang, Firdaus (Civiliza Publishing, 2025)
The socialization of applied physics textbook writing conducted for teachers of Padang Shipping Vocational High School is a strategic effort to improve the quality of vocational education in the shipping sector, particularly in the realm of physics which is directly related to the technical and practical aspects of shipping operations. This activity is designed to provide a deep understanding of the importance of developing teaching materials that are not only theory-oriented, but also able to integrate real-world applications of physics concepts in the context of the shipping world. In addition, this socialization also serves as a forum for exchanging experiences, discussing curriculum needs, and challenges faced by teachers in compiling textbooks that are in accordance with national standards and the needs of the shipping industry. Through this program, it is hoped that teachers of Padang Shipping Vocational High School can create high-quality, relevant, and contextual teaching materials, thereby increasing the effectiveness of learning and the competency of vocational high school graduates who are ready to compete in the world of work.